Leadership in organizations - Yukl, Gary A. 1940- (Pearson Education Limited, 2013)
For undergraduate and graduate-level courses in Leadership. An exploration of what makes an effective leader. Leadership in Organizations provides a balance of theory and practice as it surveys the major theories and research on leadership and managerial effectiveness in formal organizations. The eighth edition includes new examples, citations, and guidelines, and has been enhanced for better clarity and presentation